Open Networks, Closed Regimes : the Impact of the Internet on Authoritarian Rule. - Kalathil, Shanthi (Carnegie Endowment for International Peace, 2010)
As the Internet diffuses across the globe, many have come to believe that the technology poses an insurmountable threat to authoritarian rule. Grounded in the Internet's early libertarian culture and predicated on anecdotes pulled from diverse political climates, this conventional wisdom has informed the views of policymakers, business leaders, and media pundits alike. Yet few studies have sought to systematically analyze the exact ways in which Internet use may lay the basis for political change. In O pen Networks, Closed Regimes, the authors take a comprehensive look at how a broad.